Determining Core Components in Accreditation of Limited Surgery Facilities in Iran: - Asgari, Nader; Hessam, Somayeh; Masoudi Asl, Irvan; Vahdat, Shaghayegh (Galen Medical Journal, 2020)
Background: Limited surgery facilities, or day-care centers, have been expanding in recent years with the approach of reducing the number of patients referred to hospitals for treatment in relation to limited and ambulatory surgeries. This study was conducted to perform a comparative review of accreditation models for limited surgery facilities of selected countries and to obtain expert opinions in the field of policymaking and accreditation in Iran. Materials and Methods: This applied and qualitative study was carried out by a comparative method in 2019. The accreditation standards of limited surgery facilities in nine selected countries/states were assessed. Semi-structured interviews were then held with 25 Iranian experts in policymaking as well as accreditation authorities. Results: Evaluation of the core components of accreditation standards for limited surgery facilities in selected countries showed that the main concepts of care and treatment, human resource management, patient safety, drug management, patient education, health information management, quality improvement, service recipient rights, infection prevention and control, physical structure, management and leadership, and general facilities were among the key recurring concepts in all models. In the study of factors affecting the accreditation model of limited surgery facilities in Iran, 5 main topics and 43 subtopics were identified. Conclusion: Although the current assessment model of limited surgery facilities is an appropriate tool for evaluation, it still needs to be improved because of the uncertainty of evaluation model, training of accreditors and the content of standards. [GMJ.2020;9:e1729]